Draft Annual Plan 1988-89 Vol. I (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1987)
The approved outlay for Seventh Five Year Plan 1985-90 is Rs. 2900 crores. During 1987-88 an outlay of Rs. 585.75 crores was agreed which included Rs. 74 crores for Satluj Yamuna Link Canal. Keeping in view the objectives set out in the Seventh Plan and essential minimum requirements for keeping up the tempo of overall development an outlay of Rs. 610.00 crores has been proposed for Annual Plan 1988-89.
Planning Department, Government of Haryana